Stability estimation through multivariate approach among solasodine-rich lines of Solanum khasianum (C.B. Clarke): an important industrial plant - Begum, Twahira; Munda, Sunita; Gupta, Tanmita; Gogoi, Roktim; Choubey, Vikash Kumar; Chanda, Sanjoy K.; Lekhak, Himangshu; Sastry, G. N.; Lal, Mohan (Frontiers in Plant Science, 2023)
Solanum khasianum is a medicinally important plant that is a source of steroidal alkaloids ‘solasodine.’ It has various industrial applications, including oral contraceptives and other pharmaceutical uses. The present study was based on 186 germplasm of S. khasianum, which were analyzed for the stability of economically important traits like solasodine content and fruit yield. The collected germplasm was planted during Kharif 2018, 2019, and 2020 in RCBD with three replications at the experimental farm of CSIR-NEIST, Jorhat, Assam, India. A multivariate approach for stability analysis was applied to identify stable germplasm of S. khasianum for economically important traits. The germplasm was analyzed for additive main effects and multiplicative interaction (AMMI), GGE biplot, multi-trait stability index, and Shukla’s variance which were evaluated for three environments. The AMMI ANOVA revealed significant GE interaction for all the studied traits. The stable and high-yielding germplasm was identified from the AMMI biplot, GGE biplot, Shukla’s variance value, and MTSI plot analysis. Lines no. 90, 85, 70, 107, and 62 were identified as highly stable fruit yielders while, lines no. 1, 146, and 68 were identified as stable high solasodine lines. However, considering both traits, i.e., high fruit yield and solasodine content, MTSI analysis was performed which showed that lines 1, 85, 70,155, 71, 114, 65, 86, 62, 116, 32, and 182 could be used in a breeding program. Thus, this identified germplasm can be considered for further varietal development and could be used in a breeding program. The findings of the present study would be beneficial for the S. khasianum breeding program.